2020
DOI: 10.1002/ehf2.12901
|View full text |Cite
|
Sign up to set email alerts
|

Poor prognosis of heart failure patients with in‐hospital worsening renal function and elevated BNP at discharge

Abstract: Aims Our purpose was to investigate the association between the B-type natriuretic peptide (BNP) level at discharge, the occurrence of worsening renal function (WRF), and long-term outcomes in patients with heart failure (HF). Methods and results We enrolled hospitalized acute HF patients. We divided patients into four groups on the basis of BNP <250 pg/mL (BNPÀ) or BNP ≥250 pg/mL (BNP+) at discharge and the occurrence of WRF during admission: BNPÀ/WRFÀ, BNPÀ/WRF+, BNP+/WRFÀ, and BNP+/WRF+. We evaluated the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Our study confirms previous observations that patients with low (<250 pg/mL) BNP values are at very low risk of events within six months after discharge [ 11 , 12 , 13 ]. Among this cohort of low-risk patients, a combination of plasma BNP and serum creatinine allows us to separate patients with residual risk from those at very low risk (<5%) of events.…”
Section: Discussionsupporting
confidence: 92%
“…Our study confirms previous observations that patients with low (<250 pg/mL) BNP values are at very low risk of events within six months after discharge [ 11 , 12 , 13 ]. Among this cohort of low-risk patients, a combination of plasma BNP and serum creatinine allows us to separate patients with residual risk from those at very low risk (<5%) of events.…”
Section: Discussionsupporting
confidence: 92%
“…Many investigators have confirmed that cardiovascular event is the main cause of death in patients with CKD [ 40 , 41 ]. When the kidney function stage is lower than CKD stage 2, the risk of cardiovascular events will increase as the stages of renal failure increase [ 42 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…CRS is a common clinical syndrome, and it includes 5 types (type 1, type 2, type 3, type 4, and type 5) ( 10 ). Besides, CRS3 (acute cardiac failure caused by acute renal failure) and CRS4 (chronic cardiac failure caused by chronic renal failure) have been frequently observed in patients with kidney disease, and renal failure was a poor prognostic factor of CRS patients ( 11 ).…”
Section: Discussionmentioning
confidence: 99%